Fragments of international history. The Ustica tragedy and the relationship between Italy, Libya and Malta during the summer of 1980 (Rivista di Studi e Ricerche sulla criminalità organizzata, 2017)
This essay examines a fragment of the complex historical contest in which the Ustica plane crash happened. Some journalistic theories allege today that Qaddafi’s hand was behind Ustica plane crash and Bologna bombing. Based on a remarkable amount of primary sources from Italy and abroad, this essay examines the Rome-Valletta-Tripoli triangle in the summer of 1980, when Italy undertook to guarantee Malta’s neutrality, damaging Qaddafi’s interests in that strategical Mediterranean crossroad.Keywords:  Ustica, Italy, Malta, Libya, Mediterranean